(untitled) (UNED Research Journal, 2021)
Introduction: The spatial and temporal variation of the food resource in ecosystems causes discrepancies in the plant-hummingbird functional structure that affect the particular assembly roles. Objective: To evaluate the nectar production and concentration patterns in wild flowers visited by hummingbirds at several elevations over the Cordillera de Talamanca. Methods: Collection of nectar from flowers bagged with a fine mesh for 24 hours at three elevations: high, low and medium. Measurement of flower morphology for each sampled flower, taking temperature, air and soil humidity.Experiments with nectar variations. Results: There is a high variability in nectar production between species and families, associated with the presence of nectar thieves, energy saving strategy and evaporation. At low and medium elevation sites, higher altitudes had lower nectar concentrations, but flowers at higher elevations had more sugary nectar. The smaller flowers produce greater volume and greater concentration. These hummingbirds prefered sweeter nectars, and there was greater visitation at the higher elevation, which is affected by hierarchical behavior and the need for the pollinator. Conclusion: The energy resource for hummingbirds is limited by the morphological barriers between the corollas and the type of beak, the geographic reduction in nectar volume and the competition between species.